Amyloid precursor protein and amyloid precursor‐like protein 2 have distinct roles in modulating myelination, demyelination, and remyelination of axons. Issue 3 (2nd December 2018) - Truong, Phan H.; Ciccotosto, Giuseppe D.; Merson, Tobias D.; Spoerri, Loredana; Chuei, Mun Joo; Ayers, Margaret; Xing, Yao Lulu; Emery, Ben; Cappai, Roberto
Abstract: The identification of factors that regulate myelination provides important insight into the molecular mechanisms that coordinate nervous system development and myelin regeneration after injury. In this study, we investigated the role of amyloid precursor protein (APP) and its paralogue amyloid precursor‐like protein 2 (APLP2) in myelination using APP and APLP2 knockout (KO) mice. Given that BACE1 regulates myelination and myelin sheath thickness in both the peripheral and central nervous systems, we sought to determine if APP and APLP2, as alternate BACE1 substrates, also modulate myelination, and therefore provide a better understanding of the events regulating axonal myelination. In the peripheral nervous system, we identified that adult, but not juvenile KO mice, have lower densities of myelinated axons in their sciatic nerves while in the central nervous system, axons within both the optic nerves and corpus callosum of both KO mice were significantly hypomyelinated compared to wild‐type (WT) controls. Biochemical analysis demonstrated significant increases in BACE1 and myelin oligodendrocyte glycoprotein and decreased NRG1 and proteolipid protein levels in both KO brain tissue. The acute cuprizone model of demyelination/remyelination revealed that whereas axons in the corpus callosum of WT and APLP2‐KO mice underwent similar degrees of demyelination and subsequent remyelination, the myelinated callosal axons in APP‐KO mice were less susceptible to cuprizone‐induced demyelination and showed a failure in remyelination after cuprizone withdrawal. These data identified APP and APLP2 as modulators of normal myelination and demyelination/remyelination conditions. Deletion of APP and APLP2 identifies novel interplays between the BACE1 substrates in the regulation of myelination. Main Points: APP and APLP2 play important and distinct roles in CNS/PNS myelination, demyelination and re‐myelination. APP‐KO and APLP2‐KO mice have significantly less myelinated axons. APP‐KO mice are less susceptible to cuprizone‐induced demyelination and have impaired remyelination.